2023
DOI: 10.1007/s10531-023-02732-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protected areas on soil nematode communities in forests of the North of Portugal

A. Carolina Duarte,
Carlos A. Guerra,
Concha Cano-Díaz
et al.

Abstract: Nature conservation policy is mainly concerned with aboveground terrestrial species and soil biodiversity has been largely ignored, resulting in a lack of information about the conservation status of most soil organisms and about the effects that nature conservation policies have on soil systems. Forests in Northern Portugal are characterized by a remarkable diversity of ecosystems and provide habitat for an enormous diversity of living organisms. This study aims to investigate whether and to what extent prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In their study, Martay and Pearce-Higgins (2020) have reported a significant decline in the bird species that rely on earthworms, due to a decline in the earthworm population. Thus, it can be concluded that the role of soil biodiversity in maintaining ecosystem health and conserving habitats for higher vertebrates is invaluable, but often gets ignored in conservation policies (Martay and Pearce-Higgins, 2020;Cui et al, 2022;Duarte et al, 2024). This oversight leads to insufficient data on the conservation status of soil organisms, raising concerns about the effectiveness of conservation areas in preserving overall ecosystem functionality.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Martay and Pearce-Higgins (2020) have reported a significant decline in the bird species that rely on earthworms, due to a decline in the earthworm population. Thus, it can be concluded that the role of soil biodiversity in maintaining ecosystem health and conserving habitats for higher vertebrates is invaluable, but often gets ignored in conservation policies (Martay and Pearce-Higgins, 2020;Cui et al, 2022;Duarte et al, 2024). This oversight leads to insufficient data on the conservation status of soil organisms, raising concerns about the effectiveness of conservation areas in preserving overall ecosystem functionality.…”
Section: Introductionmentioning
confidence: 99%